2013
DOI: 10.7150/ijbs.5711
|View full text |Cite
|
Sign up to set email alerts
|

B19, a Novel Monocarbonyl Analogue of Curcumin, Induces Human Ovarian Cancer Cell Apoptosis via Activation of Endoplasmic Reticulum Stress and the Autophagy Signaling Pathway

Abstract: Background: The unfolded protein response, autophagy and endoplasmic reticulum (ER) stress-induced apoptosis regulate tumor cell fate and have become novel signaling targets for the development of cancer therapeutic drugs. Curcumin has been used to treat several different cancers, including ovarian cancer, in clinical trials and research; however, the role of ER stress and autophagy in the therapeutic effects of curcumin and new curcumin analogues remains unclear.Methods: Cell viability was determined using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 42 publications
1
41
0
Order By: Relevance
“…Curcumin is a natural polyphenol derived from the herb Curcuma longa that suppresses the growth of various types of cancer cells by regulating autophagy [20][21][22][23]. Although poor bioavailability in vivo limits its clinical applications, curcumin remains a good lead compound for further structure modification, as an increasing number of curcumin analogs or derivatives have been reported to induce autophagy and kill cancer cells [24][25][26]. Several studies have demonstrated that curcumin is capable of inducing autophagy in different lines of human tumor and normal cells [22,23,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a natural polyphenol derived from the herb Curcuma longa that suppresses the growth of various types of cancer cells by regulating autophagy [20][21][22][23]. Although poor bioavailability in vivo limits its clinical applications, curcumin remains a good lead compound for further structure modification, as an increasing number of curcumin analogs or derivatives have been reported to induce autophagy and kill cancer cells [24][25][26]. Several studies have demonstrated that curcumin is capable of inducing autophagy in different lines of human tumor and normal cells [22,23,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…3A and B). The activation of IRE1a, PERK and ATF6 has been reported to increase CHOP protein expression, activating and initiating the ER stressinduced apoptotic cascade (Qu et al, 2013;Chen et al, 2014;Liu et al, 2014;Yang et al, 2014). We observed that the protein expression levels of IRE1a and CHOP were increased after treatment with SC-E in HepG2 cells.…”
Section: Discussionmentioning
confidence: 47%
“…As a curcumin analogue with greater bioavailability and biological activity, EF24 is able to inhibit proliferation of colon cancer cells and migratory of melanoma cells [27, 28]. Another curcumin analogue, B19, is also found to exert antiangiogenic activity and induce apoptosis of ovarian cancer cells [29, 30]. However, their toxicities towards normal cells are always neglected.…”
Section: Discussionmentioning
confidence: 99%